Synthesis, Characterization, and In Vitro Cytotoxicity Evaluation of Doxorubicin-Loaded Magnetite Nanoparticles on Triple-Negative Breast Cancer Cell Lines - Jano Markhulia; Shalva Kekutia; Vladimer Mikelashvili; Liana Saneblidze; Tamar Tsertsvadze; Nino Maisuradze; Nino Leladze; Zsolt Czigány; László Almásy (MDPI AG, 2023)
In this study, we investigated the cytotoxicity of doxorubicin (DOX)-loaded magnetic nanofluids on 4T1 mouse tumor epithelial cells and MDA-MB-468 human triple-negative breast cancer (TNBC) cells. Superparamagnetic iron oxide nanoparticles were synthesized using sonochemical coprecipitation by applying electrohydraulic discharge treatment (EHD) in an automated chemical reactor, modified with citric acid and loaded with DOX. The resulting magnetic nanofluids exhibited strong magnetic properties and maintained sedimentation stability in physiological pH conditions. The obtained samples were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy, UV-spectrophotometry, dynamic light scattering (DLS), electrophoretic light scattering (ELS), vibrating sample magnetometry (VSM), and transmission electron microscopy (TEM). In vitro studies using the MTT method revealed a synergistic effect of the DOX-loaded citric-acid-modified magnetic nanoparticles on the inhibition of cancer cell growth and proliferation compared to treatment with pure DOX. The combination of the drug and magnetic nanosystem showed promising potential for targeted drug delivery, with the possibility of optimizing the dosage to reduce side-effects and enhance the cytotoxic effect on cancer cells. The nanoparticles' cytotoxic effects were attributed to the generation of reactive oxygen species and the enhancement of DOX-induced apoptosis. The findings suggest a novel approach for enhancing the therapeutic efficacy of anticancer drugs and reducing their associated side-effects. Overall, the results demonstrate the potential of DOX-loaded citric-acid-modified magnetic nanoparticles as a promising strategy in tumor therapy, and provide insights into their synergistic effects.